Novel Long-acting Pharmacotherapy for Exudative Age Related Macular Degeneration - Moisseiev, Elad; Loewenstein, Anat (Current Pharmaceutical Design, 2018)
Exudative age-related macular degeneration (AMD) is a major indication for the administration of intravitreal injections of anti-VEGF agents, which have been established as a very effective pharmacotherapy for this disease. However, treatment with anti-VEGF agents requires several patient visits for monitoring and treatment. Strategies for achieving a longer duration of pharmacological action are currently being developed. These include the development of longer-acting drugs, and of novel technologies to increase the duration of action of administered agents. This manuscript will review the novel drugs and technologies currently being developed for achieving a longer-action pharmacotherapy for exudative AMD.
Keywords: long acting